1999
DOI: 10.1017/s0021859699006644
|View full text |Cite
|
Sign up to set email alerts
|

Meat production from female goat kids compared with males

Abstract: Twelve female desert goat kids and an equal number of males were used to study meat production potential of desert goats at Kuku Research Station, Khartoum North, Sudan. The kids were kept in two separate groups according to sex. Kids were fed ad libitum a complete diet (a concentrate mix and green lucerne) for 147 days from 12 July to 10 Oct 1997.Male kids consumed more dry matter, had significantly greater liveweight gain and had heavier slaughter weight and superior feed conversion efficiency than femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Goats are known to be hardy and prolific animals that survive in various climatic zones and produce under different systems of husbandry (El Muola et al, 1999). Goat is a good source of lean meat with desirable fatty acids, since goats deposit relatively higher proportion of polyunsaturated fatty acids compared to other ruminants (Banskalieva et al, 2000;Mushi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Goats are known to be hardy and prolific animals that survive in various climatic zones and produce under different systems of husbandry (El Muola et al, 1999). Goat is a good source of lean meat with desirable fatty acids, since goats deposit relatively higher proportion of polyunsaturated fatty acids compared to other ruminants (Banskalieva et al, 2000;Mushi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In a meta-analysis on 11 publications done by Luo et al ( 2004 ) on dairy and meat (≥ 50% Boer) goats, the authors found growth rates of 158 g/day for meat-type goats and 138 g/day for dairy-type goats. Male animals are also generally superior to female animals of the same breed in terms of growth rate (Van Niekerk and Casey 1988 ; El Muola et al 1999 ), as is seen in Fig. 3 with a higher growth rate exhibited by castrates than does.…”
Section: Discussionmentioning
confidence: 80%
“…Sheep are generally superior to goats in terms of growth rate (El Khidir et al, 1998;Sheridan et al, 2003). Male animals are also generally superior to female animals of the same breed in terms of growth rate (Van Niekerk El Muola et al, 1999), as is seen in Fig. 1 (2020) Boer goats were only reared to 266 days of age with the highest end weights reported for the medium energy diet (49.6 kg).…”
Section: Discussionmentioning
confidence: 92%